Influence of Principle Parameters on the Average Stiffness of Optical Tweezer Using Pulsed Gaussian Beams - Quy, Ho Quang; Hai, Hoang Dinh; Nam, Hoang Van (Communications in Physics, 2011)
In this article expresions used to simulate the trap stiffness k of the optical trap are derived. The influence of principle parameters as total energy, beam waist and duration of pulsed laser beam, radius of dielectric particle, and viscosity of surrounding medium on the stiffness  is simulated and discussed.